Asthma among adult patients presenting with dyspnea to the emergency department: An observational study. (24th March 2018) - Kuan, Win Sen; Craig, Simon; Kelly, Anne‐Maree; Keijzers, Gerben; Klim, Sharon; Graham, Colin A; Jones, Peter; Holdgate, Anna; Lawoko, Charles; Laribi, Said
Abstract: Introduction: Shortness of breath is a common presenting symptom to the emergency department (ED) that can arise from a myriad of possible diagnoses. Asthma is one of the major causes. Objective: The aim of this study was to describe the demographic features, clinical characteristics, management and outcomes of adults with an ED diagnosis of asthma who presented to an ED in the Asia Pacific region with a principal symptom of dyspnea. Methods: Planned sub‐study of patients with an ED diagnosis of asthma identified in the Asia, Australia and New Zealand Dyspnoea in Emergency Departments (AANZDEM) study. AANZDEM was a prospective cohort study conducted in 46 EDs in Australia, New Zealand, Singapore, Hong Kong and Malaysia over three 72 hour periods in May, August and October 2014. Primary outcomes were patient epidemiology, clinical features, treatment and outcomes (hospital length of stay (LOS) and mortality). Results: Of the 3044 patients with dyspnea, 387 (12.7%) patients had an ED diagnosis of asthma. The median age was 45 years, 60.1% were female, 16.1% were active or recent smokers and 30.4% arrived by ambulance. Inhaled bronchodilator therapy was initiated in 88.1% of patients, and 66.9% received both inhaled bronchodilators and systemic corticosteroids. After treatment in the ED, 65.4% were discharged. No death was reported. Conclusion: Asthma is common among patients presenting with a principal symptom of dyspnea in the ED of the Asia Pacific region. There was a suboptimal adherence to international guidelines on investigations and treatments of acute asthma exacerbations presenting an opportunity to improve the efficiency of care.